In a Trance: On Paleo Art - Skoblow, Jeffrey (punctum books, 2014)
In a Trance is just the sort of genre-defying work we at Peanut and punctum and, as it happens, Jeffrey Skoblow, revel in. It is a book-length essay by a fiction writer. It is a fictional essay by a literary scholar. It is a gallant assay by a smart man who thinks while he walks, and he walks a lot. The book is a meta-meditation on Paleolithic cave drawings and the humans who ponder them. It is fact-based and entrancing just as the cave drawings are actual (existing in time - loosely - and space - more definitively) and mesmerizing. Skoblow is devising stories as "we" (humans) have always devised stories though in a less familiar mode, along a less travelled path. The essay draws on (!) the careful/thoughtful/whimsical notebooks kept by Skoblow over a dozen years. The notebooks record/illuminate/complicate his visits to twelve Paleolithic art sites as well as his deep, eccentric reading of texts concerned in some way with the subject of cave drawings by an array of scientists, anthropologists, archeologists, art historians, and other sundry enthusiasts and experts, so-called and otherwise.